A randomized, open-labelled study of the sedative, analgesic and anxiolytic effect of dexmedetomidine and tramadol in postoperative patients - L, Padma; R., Manasa C.; ., Shivshankar; Ramanujam, Ranjani (International Journal of Basic & Clinical Pharmacology, 2017)
Background: In the post-operative period, it has always been an important consideration for clinicians, to keep the patient comfortable, calm and pain free. So there is a constant need for an ideal sedative for postoperative patients. Alpha 2 adrenoreceptor agonists such as dexmedetomidine could provide an answer to this problem because they have several relevant physiological properties like sedation, anxiolysis, analgesia and arousability. This prospective, randomized trial was conducted to compare the safety and efficacy of dexmedetomidine and tramadol in the management of postoperative pain. Methods: In the present study 60 patients operated under general anaesthesia with a pain score of 1-3 were randomly allocated into two groups to receive either dexmedetomidine (group D) or tramadol (group T). In both groups, pain score, sedation score, heart rate, blood pressure, SPO2, respiratory rate were monitored for every 5 min for first 30 min, every 10 min for next 1hr, every 15 min for next 1 h, every 30 min for the next 1 h, every 1 h for 3 h and 6th hourly till 24 h. The need for rescue analgesic was also noted. The data were tabulated and analysed using descriptive statistical tool. Mean, standard deviation and comparison between the groups was done by student’s ‘t’ test. A p value less than 0.0001 was considered significant. Results: Mean duration of sedation of dexmedetomidine was 129.6±41.02 and for tramadol was 117.3 ± 47.75 (p=0.14), mean degree of sedation in both group was -1, mean duration of analgesia 139 min in Group D and 280 min in Group T (p<0.0001), rescue analgesia was required at 169th min in Group D and 288th min in Group T (p<0.0001), mean heart rate in Group D was 67.8±5.24 and 69.4±4.79 (p=0.12), mean Mean Arterial Pressure (MAP) in Group D was 78.0±8.97 and in Group T was 89.2±10.63 (p<0.00001), mean respiratory rate in Group D was 15.8±2.33 and in Group T was 15.9±2.09 (p=0.41), mean SPO2 in Group D was 99.5±0.56 and in Group T was 99.4±0.62 (p=0.14). There was no significant difference in degree and duration of sedation, duration of analgesia, vital parameters, and adverse effects in both groups but there was a statistical difference in the duration of analgesia and the need for rescue analgesia in Group D. Conclusion: Though there is no statistical difference in both groups, dexmedetomidine significantly reduced anxiety, agitation and produced calmness in postoperative patients which was not seen with tramadol.